PENALARAN HUKUM HAKIM DALAM MENERAPKAN PRINSIP STRICT LIABILITY TERHADAP PERKARA KEBAKARAN HUTAN - Hera Alvina Satriawan; M. Hotibul Islami; Yudi Pratama Putra (Komisi Yudisial RI, 2025)
This study analyses the application of the principle of strict liability in Judgment Number 456/Pdt.G-LH/2016/PN.Jkt.Sel concerning environmental litigation in Indonesia. The a quo case arose from a claim for damages and environmental restoration filed by the Ministry of Environment and Forestry of the Republic of Indonesia against PT Waringin Agro Jaya for allegedly failing to control forest and peatland fires in Ogan Komering Ilir Regency, South Sumatra Province, resulting in substantial environmental damage. In its ruling, the panel of judges not only granted the claim in part but also ordered the defendant to pay damages and undertake environmental restoration, thereby giving effect to the principle of strict liability. This study focuses on the judicial reasoning underlying the application of the principle of strict liability to achieve substantive justice, as well as the legal reasoning adopted by the court in deciding the case. This study employs a normative legal research method using statutory, conceptual, comparative, and case-study approaches to provide a more holistic analysis. The findings indicate that the panel of judges adopted a progressive and consistent approach in applying the principle of strict liability, thereby contributing to environmental protection by imposing strict liability on business actors. Nevertheless, the study also identifies ambiguity in the judicial reasoning concerning the determination of environmental restoration costs, which ultimately affects legal certainty and the effective implementation of the judgment.